Emergency politics in the third wave of democracy : a study of regimes of exception in Bolivia, Ecuador, and Peru - Wright, Claire (Political scientist) (Lexington Books, 2015)
"This book offers a thorough review of existing literature on emergency politics, offering conceptual clarification, identifying three types or paradigms of emergency politics (repressive, administrative, and disaster) and pointing to regimes of exception as a useful route to their study. It also provides an overview of emergency politics in Latin America throughout history, pointing to the predominance of regimes of exception and the repressive paradigm. The book describes the continuity of the repressive paradigm in Peruvian emergency politics to deal with both social protest and the apparent threat of organized crime and terrorism, as well as how Bolivia has shifted from a repressive to a disaster paradigm in the face of pressure to deal with climate change. It also analyzes the predominance of an administrative paradigm in Ecuadorian emergency politics in the context of weak institutions and difficulties in implementing policy as well as a populist style of leadership. Ultimately, the book offers some "best practices" in relation to the design and use of regimes of exception in democratic contexts. "--Publisher's website.